Impact of Human Resource Management Practices on Employee Retention in Nepalese Commercial Banks - Shah, Monika (Nepalese Journal of Management, 2024)
This study analyzed the impact of human resource management practices on employee retention in Nepalese commercial banks. The dependent variable selected for the study is employee retention. Similarly, the selected independent variables are organizational culture, training and development, reward and compensation, performance appraisal, work environment and employee empowerment. The primary source of data is used to assess the opinions of the respondents regarding organizational culture, training and development, reward and compensation, performance appraisal, work environment and empowerment in Nepalese commercial banks. The study is based on primary data of 135 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of human resource practices on employee retention in Nepalese commercial banks. The study showed that organizational culture, training and development, reward and compensation have positive impact on employee retention. It implies that better organizational culture leads to increase in employee retention. Similarly, it also shows that better training and development in the organization leads to increase in employee retention. Moreover, attractive rewards and compensation lead to increase in employee retention. Furthermore, performance appraisal has a positive impact on employee performance indicating that better performance appraisal in the organizations leads to increase in employee retention. Similarly, the result also showed that the working environment has a positive impact on employee retention. It indicates that better the work environment, higher would be the employee retention. Moreover, employee empowerment has a positive impact on employee retention. It implies that increase in employee empowerment leads to increase in employee retention.